2013
DOI: 10.3389/fimmu.2013.00228
|View full text |Cite
|
Sign up to set email alerts
|

Arginase 1: An Unexpected Mediator of Pulmonary Capillary Barrier Dysfunction in Models of Acute Lung Injury

Abstract: The integrity of epithelial and endothelial barriers in the lower airspaces of the lungs has to be tightly regulated, in order to prevent leakage and to assure efficient gas exchange between the alveoli and capillaries. Both G− and G+ bacterial toxins, such as lipopolysaccharide and pneumolysin, respectively, can be released in high concentrations within the pulmonary compartments upon antibiotic treatment of patients suffering from acute respiratory distress syndrome (ARDS) or severe pneumonia. These toxins a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 69 publications
2
28
0
Order By: Relevance
“…Next, we estimated an ability of the ORNs to affect the level of LPO products in mice lungs at the influenza virus infection and detected that the ORNs injection for prevention and treatment can decrease the level of LPO products by 20 and 15 % respectively in influenza infected mice, indicating that these ORNs probable decrease of the protein level of nos2 and xdh at the influenza virus infection. Activation of arginase in the airway epithelial cells leads to a reduction in iNOS mRNA and protein expression, as such reducing NO generation [21]. In our study, we found that influenza virus upregulated the mRNA expression arg2 (p < 0.05) and that the ORNs decrease overexpression of this gene at the influenza virus infection.…”
Section: Fig 2 Decrease Level Of Lpo Products In Lung Of Influenza supporting
confidence: 52%
“…Next, we estimated an ability of the ORNs to affect the level of LPO products in mice lungs at the influenza virus infection and detected that the ORNs injection for prevention and treatment can decrease the level of LPO products by 20 and 15 % respectively in influenza infected mice, indicating that these ORNs probable decrease of the protein level of nos2 and xdh at the influenza virus infection. Activation of arginase in the airway epithelial cells leads to a reduction in iNOS mRNA and protein expression, as such reducing NO generation [21]. In our study, we found that influenza virus upregulated the mRNA expression arg2 (p < 0.05) and that the ORNs decrease overexpression of this gene at the influenza virus infection.…”
Section: Fig 2 Decrease Level Of Lpo Products In Lung Of Influenza supporting
confidence: 52%
“…29 To determine the contribution of individual Arg isoforms to total arginase activity in HAEC, we individually silenced Arg1 and Arg2 using adenovirally mediated shRNA transduction. Arg2 silencing inhibited total arginase activity to <25% of control levels, whereas Arg1 knockdown had little effect on total HAEC arginase activity (Online Figure IA).…”
Section: Oxldl Activates Endothelial Arg2 By Triggering Its Translocamentioning
confidence: 99%
“…Arg1 promotes cytoskeletal formation. Polyamines in the nervous system increase tubulin expression, promote cell scaffolding formation in neurons, and induce axonal extension [22][23][24]. Arg1 can block the inhibition of axonal regeneration by myelin-related inhibitors.…”
Section: Discussionmentioning
confidence: 99%